Proyecto estratégico de desarrollo productivo como construcción significativa del conocimiento, desarrollo de habilidades para el trabajo y la formación de hábitos y actitudes para la vida comunitaria y social en la unidad educativa “Tránsito Amaguaña” de la comunidad de Cachisagua, período 2012 – 2013. - Agualongo Agualongo, Elisa Flor (2013)
This research work prior to obtaining the title of Master of Educational Management , is of much importance that a detailed study is made in relation to the Strategic Project for productive development as significant building knowledge , developing skills for work and formation of habits and attitudes to community and social life in the "Transit Amaguaña" Educational Unit Cachisagua community, parish of St. Simon, canton Garand, in order to encourage students of that school to make organic production projects , livestock and craft. The application of integrated production projects family gardening is an appropriate alternative for families of students in this field, produced and consumed at low cost, fresh and healthy products for a balanced diet, our goal is that all persons have means of access this benefit, it is nutritionally adequate in terms of quality , quantity and variety and we are sure it will be accepted in its cultural context , achieving a population that can be considered "safe to food level." The “Transit Amaguaña " Educational Unit has sights on making food projects fun and educational autonomy between different populations of students, peasants industry , academic institution etc. . , Implementing participatory methodologies in order to generate appropriate knowledge both individually and collective . All this about technical training workshops planting and alternative food processing , through the assembly of gardens, plots, treatment of water for domestic consumption and other agro ecological practices , development of indigenous food sector , following a study analysis soil. The thesis focused on the analysis of the feasibility of strategic projects in the productive areas of land available to the school. The research will improve the agricultural, livestock and handicraft production with the active participation of students and parents of the "Transit Amaguaña " Educational Unit Cachisagua community . XII I also propose training to all teachers, parents and students as a strategy to develop productive projects. The methodology of this research will contribute to the field of education, since it aims to determine the efficacy results of the aforementioned production projects. The thesis focused on the analysis of the implementation of strategic projects for productive development and skills development for community and social work in said Education Unit Cachisagua community. The theoretical, psychological foundations, educational foundations, legal bases and the definition of key terms is provided in Chapter I. An ongoing relationship between the two variables in order for you to go combining both theory and actual practice of what has been proposed in order to implement the above projects is established. Chapter II is put into consideration the methodology applied in the research process; this is the type of investigation, procedure, sample and data collection technique. I should point out that the research was based on different methods, under its application gave me the most appropriate method according to the characteristics that allowed me to discover, understand and explain the behavior of the chosen population universe, to the survey were applied as data collection technique. Note that it was not necessary to apply any formula to determine the sample because it is a very small population universe. Chapter III relates to the analysis and interpretation of the results obtained in the implementation of the respective survey, they once were tabulated in tables and plotted represented statistically accompanied by their respective interpretation. Subsequently the hypothesis testing that helped me in developing the conclusions and recommendations are made. It is necessary to indicate that one of the conclusions , and perhaps most important , is that which determines the students and parents of the Education Unit require training as it relates to the development of productive projects. XIII Finally in the scientific paper of the thesis, my scientific test is after the teaching experience and research based on the location of the problem I've seen with the name of "Implementation of strategic projects for development of integrated production for home gardens achieve a food secure population level .